Training-intensity Distribution on Middle- and Long-distance Runners: A Systematic Review - Campos, Yuri; Casado, Arturo; Vieira, João Guilherme; Guimarães, Miller; Sant’Ana, Leandro; Leitão, Luis; da Silva, Sandro Fernandes; Silva Marques de Azevedo, Paulo Henrique; Vianna, Jeferson; Domínguez, Raúl (International Journal of Sports Medicine, 2021)
Training-intensity distribution (TID) is considered the key factor to optimize performance in endurance sports. This systematic review aimed to: I) characterize the TID typically used by middle-and long-distance runners; II) compare the effect of different types of TID on endurance performance and its physiological determinants; III) determine the extent to which different TID quantification methods can calculate same TID outcomes from a given training program. The keywords and search strategy identified 20 articles in the research databases. These articles demonstrated differences in the quantification of the different training-intensity zones among quantification methods (i. e. session-rating of perceived exertion, heart rate, blood lactate, race pace, and running speed). The studies that used greater volumes of low-intensity training such as those characterized by pyramidal and polarized TID approaches, reported greater improvements in endurance performance than those which used a threshold TID. Thus, it seems that the combination of high-volume at low-intensity (≥ 70% of overall training volume) and low-volume at threshold and high-intensity interval training (≤ 30%) is necessary to optimize endurance training adaptations in middle-and long-distance runners. Moreover, monitoring training via multiple mechanisms that systematically encompasses objective and subjective TID quantification methods can help coaches/researches to make better decisions.
Keywords: polarized training; pyramidal training; threshold training; periodization; endurance